Concepts and Spiritual Needs Assessment of Cancer Patients - แก้วมณี, ชนุกร (Nursing Journal of The Ministry of Public Health, 2019)
Cancer leads to not only physical suffering but also significant spiritual distress in patients. Cancer patients therefore require high spiritual care coupled with physical care. Moreover, care should include physical, psychological, and social dimensions to help patients with cancer who face spiritual distress and crisis, or to put patients at peace during the end stage of their lives. Therefore, understanding the dimensions of spiritual needs allows for the evaluation and provision of appropriate care for patients. This article reviews the concepts and methods for assessing spiritual need of cancer patients for health professionals, especially registered nurses, and caregivers. When they have knowledge and understanding the concept and assessment methods, it will lead to an improvement in holistic nursing care and an appropriate response to the spiritual.